Professional Parody: An Examination of Artist Practices Parodying and Disrupting Business Models to New Ends - Mellor, Alexia (Organizational Aesthetics, 2015)
This paper identifies trends within visual arts practice in which artists have adopted corporate and organizational structures to be disrupted, blurred and interrogated. The research investigates artist projects that: parody corporations with the aim of ’identity correction’, expose, critique and reveal the proliferation of corporate and legal language in culture; and mimic emerging business models with the intention of disrupting them in order to be applied in new ways to new contexts. Considering Delueze and Guattari’s concepts of deterritorialization and the rhizome, this research suggests that art practices borrowing from business culture serve to simultaneously disrupt and recontextualize economic systems while offering opportunities to make new, unexpected connections. Beginning with a discussion of Conceptual art practices of the 1960s, this research explores ways artists have coopted and pushed the boundaries of business practices within the context of global capitalism. It proposes the term "re:organizational aesthetics" to describe recent aesthetic developments of artists repurposing business models, and concludes with the suggestion that such practices are paving the way for us to redesign our economic and cultural landscapes.